Por que a litigância aumentou?: avaliação de algumas hipóteses da literatura por meio das estatísticas históricas do Judiciário - Hugo Freitas Reis (2022)
The present study attempts to identify possible extrajudicial causes for the increase in litigiousness that occurred in Brazil. Firstly, justification is given for the object of study, through a demonstration that judicial efficiency can exert an influence over development. It is then shown that many studies point to Brazil performing poorly in this aspect, therefore justifying the utility of investigating the causes behind the increase in demand for the courts, as an aid to addressing the problem. Historical statistics are gathered for the number of suits filed to the Brazilian Supreme Federal Court, to the Labor Justice and to the justice system as a whole, thereby demonstrating the increase in litigiousness, especially in the 1990’s. Hypotheses raised by legal scholars for the causes behind such an increase are then collected, with some of them being subsequently put to a correlation test against the time series measuring the number of suits filed per capita. The results thus obtained point to the increase in litigiousness correlating with an Increase in GDP per capita, in the proportion of Brazilians living in urban areas, in the length of the constitution in force and in the number of rights provisioned.